Designing a strain gauge transducer for dynamic load measurement in cycling using numerical simulation - Drouet, J.-M.; Champoux, Y. (Procedia Engineering, 2014)
The aim of this work is to study the effect of a beam transducer's modal behaviour, suspended mass and system damping on the load measurement accuracy using base excitation, and to provide insight to engineers on the process of designing a strain gauge beam transducer to measure dynamic loads. Development and results for a simple beam transducer and an instrumented brake hood and seat post are presented. One of the main conclusions to be drawn from the results presented is that, in the case of base excitation, the transducer's first bending mode has no negative effect on the measurement accuracy.